A Comparative Analysis of Wage Policies for Workers in Indonesia and Australia: Their Impact on Worker Welfare - Putri, Rahma Nia; Wulandari, Yessika Putri; Pramesti, Al Misse Syarivatul Sukma; Sugiatama, Muhammad Ardian; Faqih, Muhammad Yusron (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2025)
This study presents a comparative analysis of wage policies in Indonesia and Australia, focusing on their impact on worker welfare. Wages, as compensation for labor, are a crucial component of ensuring a decent standard of living. Using a comparative approach, this research explores how economic, social, and institutional factors shape wage policies in both countries. The findings show that Indonesia, as a developing country, faces challenges in setting minimum wages, which are often influenced by the needs of industrial growth and investment. In contrast, Australia's well-established wage policies and strong labor protections significantly enhance workers' socio-economic welfare. These insights provide valuable guidance for Indonesian policymakers to develop more equitable and sustainable wage policies.